Biological control in winter: novel evidence for the importance of generalist predators. Issue 1 (21st November 2014) - Pekár, Stano; Michalko, Radek; Loverre, Pamela; Líznarová, Eva; Černecká, Ľudmila; Diamond, Sarah
Summary The role of generalist predators in pest control has been neglected because generalists are not able to track pest populations. Generalist predators are suggested to be important in spring before specialist predators become active. Here, we show that some generalist predators are important even during winter, when the majority of arthropod pests and their enemies are dormant. We quantified the role of winter‐active generalist predators on the suppression of pear psylla during winter using a discrete nonlinear model of an intraguild predation system. To parameterize our model, we conducted a series of experiments on (i) functional responses, (ii) prey preferences and (iii) ontogenetic development and made observations on the population densities of spiders and potential prey. We ran the model for different winter scenarios, that is, for very cold and very warm winters. Synthesis and applications. We found that winter‐active predators considerably suppressed the pear psylla population. Predators exerted a stronger effect in a warmer winter than in a colder one. Orchard growers thus should avoid use of non‐selective pesticides during this period and instead aim to support the community of generalist predators. Our results suggest more attention should be given to encouraging generalist predator populations in other systems, even in periods when crops are not producing.